(untitled) (Altre Modernità, 2010)
The aim of this lecture is to explore the question of representing AIDS in the poetry of Hezy Leskly, namely in the book, Sotim yekarim, "Dear perverts", his fourth and last collection which has been published after his death in 1994. Contrarily to what one could have expected, representations of AIDS and references to this disease are almost totally absent from the book, except in the last poem, Yitzkhak. Nevertheless, although Hezy Leskly explicitly writes on the subject only once, AIDS, or better, the malaise generated by AIDS epidemic, permeates the whole book being an integral part of Leskly’s poetic discourse.